Multi-level governance – the eastern versions. Emerging patterns of regional developmental governance in the new member states - Bruszt, László (Journal of Public Governance, 2008)
This paper deals with emerging configurations of developmental regionalism, different patterns of multi-level governance in the CEE countries using examples from the Czech Republic, Hungary and Poland. EU conditionality and pre-accession programmes linked to the idea of a Europe of the Regions played considerable role in the changing, and in the case of some of the aspiring member countries, in the creating of regional institutional landscapes. While later, the same programmes became instigators of (re)centralization and re-nationalization, the interaction between uniform EU conditionality and diverse domestic conditions resulted in various emerging versions of NMG, different configurations of regionalism.